La contrebande des produits du tabac au Canada entre 1985 et 1994 et le cas particulier du Québec - Alain, Marc (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1997)
The professional smuggling of mass consumption products develops when demand for a product is not adequately fulfilled by the legitimate market. The difficulties encountered in supplying are, in most contemporary cases, caused by real rarity of the desired product. For other cases, however, the rarity is largely virtual in that government taxes aimed at the product in question lead to increasing the product's price to a prohibitive end. This was the case with cigarettes in Canada between 1985 and 1994. Before both, the federal and provincial, governments decided to drastically decrease cigarette taxes in February 1994, the price for a pack of cigarettes was five to six times higher than the same product in the United States. This article begins with a brief review of the contribution made by economists in regard to contemporary smuggling. Focus will be aimed at common characteristics of the smuggling phenomenon across the world. Elements which are more particular to the Canadian smuggling situation will be identified as well. While the difference in the price of cigarettes between Canada and the United States would seem to be the undeniable driving force behind the development of smuggling activities at the countries ' border, one key question remains unexplained. Why was the volume of contraband unequally distributed across Canada even though the price of cigarettes remained largely consistent throughout all provinces? The level of organization of smuggling networks was much higher in Eastern Canada, and particularly in Quebec, than it was in the western provinces. It is argued that the reasons for this are not only due to price, but to a series of political, historical, and geographical factors which allowed cigarette smugglers to function better in Quebec than in the rest of the country.